Взаимодействие нанопорошка алюминия с водным раствором соли марганца (II) - Грязнова Е. Н. Елена Николаевна; Шиян Л. Н. Людмила Николаевна; Лобанова Г. Л. Галина Леонидовна; Яворовский Н. А. Николай Александрович (2013, 2013)
Заглавие с экрана